A comparative study of serum ascitic fluid albumin gradient with ascitic fluid total protein in evaluating the etiology of ascites - Gopi, Manigandan; Hanifah, Mohamed (International Journal of Advances in Medicine, 2019)
Background: The traditional method of classification of ascites by AFTP offers little insight into the pathophysiology of ascites formation and it has many drawbacks. In order to overcome it, the classification of ascites based on SAAG has emerged. Even SAAG has some draw backs like non correlation with ascites due to non-alcoholic cirrhosis and difficulty in identifying the ascites due to mixed etiology. This study is conducted to compare the diagnostic accuracies of SAAG and AFTP in identifying the pathophysiology of ascites. Methods: A total of fifty patients who were admitted with ascites were included in the study. Ascitic fluid total protein and SAAG were calculated. They were classified on the basis of SAAG into High SAAG and Low SAAG and on the basis of AFTP into Transudate and Exudate. After the etiology of ascites evaluated by various diagnostic procedures, the sensitivity, specificity and diagnostic accuracy of SAAG and AFTP in identifying the pathophysiology of ascites calculated sepereately. The diagnostic accuracies of SAAG and AFTP were compared statistically. Results: The sensitivity of SAAG was found to be 86.84% and that of AFTP 60%. The specificity of SAAG was found to be 83.33% and that of AFTP was found to be 60%. The diagnostic accuracy of SAAG was found to be 86% and that of AFTP was found to be 60%. The diagnostic accuracy of SAAG and AFTP for individual etiologies of ascites were found and compared. SAAG was found to be superior to AFTP with a P value of <0.01 which was statistically significant. Conclusions: The sensitivity and specificity of SAAG was superior to AFTP in identifying the etiology of ascites.